The Real-Time Alert System for Prayers at Smart Masjid - Alam, Tanweer; Erqsous, Moath (Scientific Journal of Informatics, 2020)
Arrange and monitor people in a crowded environment inside masjid is a critical task. It is necessary to fill rows start from first row behind the Imam. Most counting techniques depend on detecting individuals in order to count their number. Counting and arrangement becomes inefficient when it is required in real-time and when the crowd is dense. I am proposing a technique for monitoring and estimating the density of crowd in real-time using infrared technology. The intelligent systems will be designed based on the number of people section wise. The mosque will be divided into sections and each section will be allocated an Infra-Red Camera. Each section will be programmed to contain limited number of people. There will be an LED display allocated to each section. With the people coming into that section, the display will start becoming less GREEN. In other words, the intensity of the GREEN LED display will become weaker. As the section is completely filled, the display will turn red. This way, people could see the section from quite a distance and can easily decide whether to move forward or not. As soon as the people enter the mosque, they will have an overview of each section and can decide to go to the suitable places to get settled easily into the rows. Our pre-programmed thermal camera will recognize people on the basis of their body temperature. The LED display will go less green as the system receives more thermograms. After reaching the highest level of thermograms received, the LED display will automatically go RED. This would naturally stop people to enter that section.